Bilingualism and cognitive reserve: It’s a matter of top-down or bottom-up process - Boutris, Panagiotis; Rees, Jessica; Bevan, Brodie; Izura, Cristina (Yearbook of the Poznan Linguistic Meeting, 2020)
Cognitive performance declines with age following different trajectories. The cognitive trade-off, however, between age and cognitive reserve is still not clear. In addition, bilingualism has been thought to play a role in delaying cognitive decline by affecting cognitive control outside the scope of language. However, the effect has been unreliably reproduced and without exploring sufficiently the differences between cognitive functions that govern language control. In the current study 112 adults varying in age, level of bilingualism and cognitive reserve, completed a modified version of the Simon task, which engaged the mechanisms of interference suppression and shifting. Using ex-Gaussian analysis, the Simon effect was replicated in the normal component and the shifting effect was found in the exponential. Additional linear mixed-effects model analysis showed a significant “negative” effect of bilingualism on inhibition and a “positive” effect of cognitive reserve on shifting, both independent of age. Age affected similarly the speed of engagement of both executive functions irrespectively of language or cognitive background. Implications of a bilingual disadvantage and a beneficial effect of cognitive reserve during ageing are discussed.